Examining 25-Year Trends of Type 1 Diabetes Incidence in Pediatric Population Aged 0-14 of the Republic of Srpska - Gordana Bukara-Radujković (Биомедицинска истраживања, 2024)
Introduction: Data on newly diagnosed cases of type 1 diabetes and the incidence of this disease are very significant. Studies like this one, with an analysis of incidence over the past 25 years, help not only locally but also globally. Methods: The primary source of data is hospital records from hospital centers in Republic of Srpska. The secondary, confirmatory source, is the data from the Health Insurance Fund of Republic of Srpska through which all newly diagnosed patients receive insulin and blood glucose testing strips. Results: The average incidence for the entire period was 12.8/100,000 (95% CI: 10.40-15.22), with a total of 527 cases, of which 265 (50.3%) were boys. Positive linear trend was observed (R=0.747, R2=0.558, p=0.000018). The annual increase was 0.59 (95% CI: 0.37- 0.82) or 29.06%. There was no difference between sexes, and the highest incidence, number, and growth were in the age group of 10-14 years. Discussion: Compared to the period 2001-2016 (11/100,000) and to the period 1998-2010 (7.5/100,000), there was the increase in incidence. Significant increase in incidence was observed in the period 2017-2022. There is no difference from the rest of the world regarding incidence by sex, but there is regarding age group, with the highest incidence in the 10-14 age group. Conclusion: This research provides a good basis for future studies on the impact of environmental, medical, and other factors on the onset of type 1 diabetes, as well as potential local, national, and global diabetes prevention programs.
Keywords: type 1 diabetes; incidence trend; pediatric patients